Settlements in the field of non-state social services under the legislation of certain foreign states: economic and legal aspect - Панова, Людмила В’ячеславівна; Панова, Л. В.; Panova, Liudmyla V.; Грамацький, Ернест Мірчевич; Грамацький, Е. М.; Hramatskyi, Ernest M.; Gramatskyy, Ernest; Панченко, Анна Олександрівна; Панченко, А. О.; Panchenko, Anna O. (Riga : Baltija Publishing, 2025)
In the context of the present conditions of wartime, decentralisation and Ukraine's approximation to the standards of the European Union, the issue of payments for social services provided by non-state structures is becoming critical. The positive experience of foreign countries demonstrates that the introduction of contracting models, voucher systems, indicative budgeting, and outsourcing of social functions significantly increases the efficiency of social protection, allowing the state to focus on strategic management, and non-governmental organisations to focus on the direct provision of services. In view of this, there is a need to conduct an in-depth analysis of such models in the international legal field, in particular in the legislation of the EU countries, African and Latin American states, and to identify universal and contextual payment mechanisms, as well as to determine their applicability to the national legislation of Ukraine. The objective of the present study is a thoroughgoing analysis of the economic and legal mechanisms for making payments in the field of social services provided by non-state providers in certain foreign countries, with a view to identifying effective models of financing, legal regulation and quality control of services that can be adapted to the Ukrainian context. The research methodology consists of the following methods: the comparative legal method, the analysis of regulatory and legal sources, the system-structural method, the method of analogies and extrapolation, and the case study method. The study analysed the economic and legal aspects of payments in the field of social services provided by non-state providers in certain foreign countries. The author conducts an analysis of models of legal regulation of relations between the state and non-state organisations that perform social functions, as well as financial mechanisms for reimbursement of the cost of services or compensation, in particular through social orders, grant financing, subventions and voucher systems. The study is based on the analysis of regulatory legal acts of the European Union countries, as well as individual states of Asia, Africa and Latin America, which vary in terms of economic development and the degree of institutional capacity of the state. This text focuses on the mechanisms of contracting services, cost-effectiveness assessment, principles of transparency, accountability and social orientation of budget financing. The authors undertake a comparative legal analysis of the applied calculation models, determining their advantages, disadvantages and possibilities of adaptation in Ukrainian conditions. In undertaking this analysis, the authors take into account the current reforms in the field of decentralisation, social protection, as well as the desire for integration into the EU legal space. Consequently, conceptual proposals have been formulated for the enhancement of Ukraine's national legislation pertaining to the financing of non-state providers of social services. These proposals are founded upon the principles of economic feasibility, legal certainty, transparency of procedures, and effectiveness.
Panova L. Settlements in the field of non-state social services under the legislation of certain foreign states: economic and legal aspect / L. Panova, E. Gramatskyy, A. Panchenko // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. - Vol. 11(3). - Р. 68-77. URL: https://doi.org/10.30525/2256-0742/2025-11-3-68-77
Keywords: non-state social services; economic and legal aspect; public-private partnership; financing mechanisms; legal regulation; state financing of NGOs; social security; outsourcing of social protection services